Do occupational therapy interventions improve quality of life in persons with dementia? A meta‐analysis with implications for future directions. Issue 2 (24th June 2016) - Ojagbemi, Akin; Owolabi, Mayowa
Abstract : Occupational therapy (OT) interventions have shown positive effects on physical functioning in persons with dementia (PwD). However, their effect on quality of life (QoL) has been inconsistent in individual clinical trials. The present review appraises current evidence for the use of OT interventions in improving QoL of PwD. Records in the Cochrane Database, MEDLINE, EMBASE, PsycINFO, and Cumulative Index to Nursing and Allied Health Literature were searched for relevant citations, and PubMed was searched for in‐process articles. Additional searches of the reference lists of retrieved articles were undertaken. Ten studies involving 1002 PwD met the criteria for syntheses. OT intervention produced small non‐significant improvements in overall QoL. The evidence from the present review does not support the specific use of OT interventions for the improvement of QoL in PwD under pragmatic clinical conditions at this time. They may be best used as part of a comprehensive range of interventions for PwD. Recommendations are made for future design of OT interventions focusing on the improvement of QoL, which is central to the well‐being of PwD.